2021
DOI: 10.3390/nu13051477
|View full text |Cite
|
Sign up to set email alerts
|

High Intakes of [6S]-5-Methyltetrahydrofolic Acid Compared with Folic Acid during Pregnancy Programs Central and Peripheral Mechanisms Favouring Increased Food Intake and Body Weight of Mature Female Offspring

Abstract: Supplementation with [6S]-5-methyltetrahydrofolic acid (MTHF) is recommended as an alternative to folic acid (FA) in prenatal supplements. This study compared equimolar gestational FA and MTHF diets on energy regulation of female offspring. Wistar rats were fed an AIN-93G diet with recommended (2 mg/kg diet) or 5-fold (5X) intakes of MTHF or FA. At weaning, female offspring were fed a 45% fat diet until 19 weeks. The 5X-MTHF offspring had higher body weight (>15%), food intake (8%), light-cycle energy expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The above evidence indicates that folate/vitaminB 12 imbalance coupled with pregnant women’s MTHFR rs1801133 CC and rs1801131 TT genotype is more likely to accumulate 5-methyl-THF in the body. Although the role of 5-methyl-THF in the pathogenesis of GDM is unclear, recent animal studies suggested that consuming 5-methyl-THF diets will increase the weight of the dams and their female offspring (35,36) . Therefore, 5-methyl-THF may play a role in GDM occurrence, and further studies are needed to clarify the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above evidence indicates that folate/vitaminB 12 imbalance coupled with pregnant women’s MTHFR rs1801133 CC and rs1801131 TT genotype is more likely to accumulate 5-methyl-THF in the body. Although the role of 5-methyl-THF in the pathogenesis of GDM is unclear, recent animal studies suggested that consuming 5-methyl-THF diets will increase the weight of the dams and their female offspring (35,36) . Therefore, 5-methyl-THF may play a role in GDM occurrence, and further studies are needed to clarify the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Accepted manuscript 5-methyl-THF diets will increase the weight of the dams and their female offspring (35,36) .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…While studies to date suggest that folate and choline may interact to influence the metabolic phenotypes, different forms of folate (folic acid or methyl folate) and choline (free choline, fat-soluble choline, or oxidized choline) should be considered when examining their programming effects. Comparisons across folate and choline forms are lacking, but different effects can be suggested from the observation that gestational intake of [6S]-5-methyltetrahydrofolic acid compared to folic acid at ×5 requirements favored increased food intake and body weight of mature female offspring [61].…”
Section: Consideration Of Folic Acid and Cholinementioning
confidence: 99%
“…[4,13] Nutrient modifications of gene methylation patterns in utero were also shown to occur after pregnant rodents are fed highfat, [14,15] protein-deficient diets, [16] or high and low methyl group vitamins. [14,15,17,18] Moreover, high-fat diets (HFD) fed to young mice lead to obesity and insulin resistance (IR) in the adulthood and associated with concurrent changes in gene methylation. [19] However, the effect of supplemental intakes of micronutrients on these changes when added to the diets of adult mice has not been described.…”
Section: Introductionmentioning
confidence: 99%